2006
DOI: 10.1088/0264-9381/23/7/024
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of 3D boson stars with waveform extraction

Abstract: Numerical results from a study of boson stars under nonspherical perturbations using a fully general relativistic 3D code are presented together with the analysis of emitted gravitational radiation. We have constructed a simulation code suitable for the study of scalar fields in space-times of general symmetry by bringing together components for addressing the initial value problem, the full evolution system and the detection and analysis of gravitational waves. Within a series of numerical simulations, we exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…They computed the dominant axial oscillation modes and found no instabilities. In analogy with previous studies of the oscillation modes of boson stars [29][30][31], they confirmed that the axial QNM spectrum of gravastars can be used to discern a gravastar from a BH. In the thin-shell limit, the axial QNM frequencies of Ref.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…They computed the dominant axial oscillation modes and found no instabilities. In analogy with previous studies of the oscillation modes of boson stars [29][30][31], they confirmed that the axial QNM spectrum of gravastars can be used to discern a gravastar from a BH. In the thin-shell limit, the axial QNM frequencies of Ref.…”
Section: Introductionsupporting
confidence: 82%
“…Building on Ryan's proposal, Kesden et al showed that the inspiral of a small compact object into a nonrotating boson star will emit a rather different gravitational waveform at the end of the evolution, when the small object falls into the central potential well of the boson star instead of disappearing into the event horizon of a BH [28]. Several authors have computed the QNM spectrum of boson stars, showing that it is remarkably different from the QNM spectrum of BHs and lending support to the feasibility of no-hair tests using QNM measurements [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…4c of Ref. [22] shows that many modes are indeed present in the signal, that the l = 2 component dominates the energy emission, and that all modes with n < 12 are necessary to fit the waveform (modes with n = 5 − 10 being dominant).…”
Section: Exotic Strawmen: Boson Star Hair Countingmentioning
confidence: 96%
“…For example, there are models of dark matter which use EKG in the weak field limit [50][51][52][53]. One example of relativistic scalar field is boson stars [54][55][56][57][58]. Therefore, it is interesting to ask if gravitational wave detection can be used to distinguish BBH collisions in f (R) theory from another system which also contains scalar fields.…”
Section: Dynamics Of the Binary Black Hole Induced By The Scalar Fieldmentioning
confidence: 99%